Gratitude as the Foundation of Educational Values in Contemporary Times: A Perspective from Surah Al-Fatihah - Fitri Lutfia Zahroh; Wasehudin; Abdul Muin (South Sulawesi Education Development (SSED), 2025)
This research focuses on contemporary Islamic education which faces many challenges, especially due to the influence of foreign cultures that are contrary to Islamic principles with information obtained from social media. The main fact in this study is the importance of the value of Gratitude contained in the letter of alfatihah as an important foundation for the formation of students' character. To understand this issue more deeply, the author applies a qualitative method with a literature research approach, including a study of academic literature, the Qur'an, and relevant hadith to expand the author's understanding of gratitude in education.The results of the study show that the integration of the value of gratitude in the educational process can help students not only in developing good morals and appreciating knowledge, but also in increasing the desire to learn through the understanding and application of the value of Gratitude, as well as in increasing their social responsibility. These findings conclude that an effective approach in teaching the value of gratitude has the potential to produce a generation that has faith, noble character, and is ready to face the challenges of the times. In addition, this generation is expected to make a positive contribution to society, creating a beneficial impact on the surrounding social environment.